Changes in Urinary Titin Fragment in Response to Different Types of Dynamic Eccentric Exercises - Lee, Minjung; Goral, Kamil; Flis, DamianJ; Skrobot, Wojciech; Cieminski, Karol; Olek, RobertA; Akimoto, Takayuki; Ziolkowski, Wieslaw (International Journal of Sports Medicine, 2020)
The urinary level of the titin fragment has been considered a non-invasive and sensitive biomarker for muscle damage in clinical cases. However, there is little evidence regarding changes in the urinary titin fragment in response to exercise-induced muscle damage. In this study, we aimed to investigate whether the urinary titin fragment reflects the magnitude of muscle damage induced by two lower-limb eccentric exercises. In this study, healthy young male subjects performed drop jump (n=9) and eccentric ergometer exercise (n=9). Blood and urine samples were collected at various time points before and after the exercises. Although perceived muscle soreness assessed by sit-to-stand tasks was increased at 24 h and 48 h after both drop jump and the eccentric ergometer exercise groups, the pressure pain threshold was not changed. Changes of the urinary titin fragment, plasma myomesin 3 fragments, creatine kinase (CK), and myoglobin (Mb) after the eccentric exercises were increased but not statistically significant. Meanwhile, we found that the changes in the urinary titin fragment levels in response to both drop jump and the eccentric ergometer exercise were correlated with those of plasma CK and Mb levels. These results provide evidence that the urinary titin fragment level is a non-invasive biomarker reflecting the magnitude of eccentric exercise-induced muscle damage.
Keywords: connectin; titin; eccentric exercise; muscle damage; biomarkers